2023
DOI: 10.1007/s00410-023-02019-7
|View full text |Cite
|
Sign up to set email alerts
|

H2-H2O immiscibility in Earth’s upper mantle

Abstract: Immiscibility between water and hydrogen-rich fluids may be responsible for the formation of super-reduced mineral assemblages and for the early oxidation of Earth´s upper mantle. In the current study, we present new data on the critical curve in the H2-H2O system to 1400 ℃ and 4 GPa. We utilized a synthetic fluid inclusion method to trap fluids at high P–T conditions within quartz and olivine crystals. Experiments were performed in a piston-cylinder type apparatus, employing a double-capsule technique. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…Soubiran & Militzer (2015) found that H and H 2 O are likely to be miscible at temperatures between 2000 and 6000 K and pressures at 10 s of GPa using ab initio simulations, and Gupta et al (2024) found H and H 2 O to be miscible at temperatures down to 650 K at ~0.01 GPa. However, some experimental studies have suggested that demixing may occur at certain pressures and temperatures (e.g., Bali et al 2013;Vlasov et al 2023). Studies of other chemical species indicate that gases and supercritical fluids are completely miscible (Budisa & Schulze-Makuch 2014;Pruteanu et al 2017), and the assumption of the miscibility of hydrogen and supercritical water has been made in previous studies of sub-Neptune interiors (Pierrehumbert 2023; Benneke et al 2024).…”
Section: Methodsmentioning
confidence: 96%
“…Soubiran & Militzer (2015) found that H and H 2 O are likely to be miscible at temperatures between 2000 and 6000 K and pressures at 10 s of GPa using ab initio simulations, and Gupta et al (2024) found H and H 2 O to be miscible at temperatures down to 650 K at ~0.01 GPa. However, some experimental studies have suggested that demixing may occur at certain pressures and temperatures (e.g., Bali et al 2013;Vlasov et al 2023). Studies of other chemical species indicate that gases and supercritical fluids are completely miscible (Budisa & Schulze-Makuch 2014;Pruteanu et al 2017), and the assumption of the miscibility of hydrogen and supercritical water has been made in previous studies of sub-Neptune interiors (Pierrehumbert 2023; Benneke et al 2024).…”
Section: Methodsmentioning
confidence: 96%